Memory traces of childhood exposure to terror attack and resilience and post-traumatic growth in adulthood. (1st March 2020) - Zeidner, Moshe; Kampler, Shlomzi
Abstract: This study examined the relationship between memory traces of exposure to terror attack during childhood and reported resilience and post-traumatic growth (PTG) in adulthood. Participants were 208 Israelis exposed to threat of terror in their early years during the second Intifada. Approximately half of the sample resided in high-risk areas for terror attack during the Second Intifada (i.e., occupied territories of Judah and Samaria) whereas the remaining half resided in relatively low risk areas (i.e., Israel proper). Participants were assessed in adulthood on measures resilience and PTG. Both objective and subjective measures of exposure to terror attack and resilience were found positively related to PTG.